1997
DOI: 10.1136/gut.41.3.411
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of hepatitis C virus in the pathogenesis of the neurological syndrome in chronic hepatitis C

Abstract: A 72 year old man developed chronic sensory neuropathy (CSN) during chronic hepatitis C (HCV) infection. Neurological symptoms began one year after acute HCV hepatitis and slowly worsened over three years. No conventional cause for CSN was found. Circulating antinervous tissue antibodies (including anti-Hu) and inflammatory infiltrates in sural nerve biopsy specimens were absent. However, the presence of anti-HCV antibody and HCV-RNA in cerebrospinal fluid indicated that HCV had reached the intrathecal compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…HCV belongs to the Flaviviridae family, which includes several neurotropic viruses [13,14]. There has been recent interest in the possibility of a link between chronic HCV infection and cognitive impairment independent of liver failure, because HCV sequences have been detected in cerebrospinal fluid (CSF) [15,16] and brain tissue [17,18] and because proton magnetic resonance spectroscopy has shown significant metabolite alterations [19,20].…”
mentioning
confidence: 99%
“…HCV belongs to the Flaviviridae family, which includes several neurotropic viruses [13,14]. There has been recent interest in the possibility of a link between chronic HCV infection and cognitive impairment independent of liver failure, because HCV sequences have been detected in cerebrospinal fluid (CSF) [15,16] and brain tissue [17,18] and because proton magnetic resonance spectroscopy has shown significant metabolite alterations [19,20].…”
mentioning
confidence: 99%
“…HCV belongs to the Flaviviridae family, which includes several well-known neurotropic viruses (e.g., yellow fever, dengue, and tick-borne encephalitis viruses), and several reports have implicated HCV as an occasional cause of various CNS and peripheral nervous system pathologies (3,6,11,13,27). Moreover, HCV RNA has been detected in cerebrospinal fluid from both HIV-positive and HIV-negative patients (23,25), and viral sequences have been amplified directly from brain tissue from a patient diagnosed with progressive encephalomyelitis (3).…”
mentioning
confidence: 99%
“…Vasculitis results from the deposition of circulating cryoglobulins and immunoglobulin M complexes containing HCV particles in vessels wall . While cryoglobulinemia‐associated vasculitis has been extensively studied in the skin, the kidney and the peripheral nervous system , little is known about the potential consequences of cryoglobulinemia on liver microcirculation and portal flow. One study has shown that among HCV‐infected patients, there was a significant increase in sinusoidal T‐cell lymphocytes in those positive for cryoglobulinemia compared to those negative for cryoglobulinemia which could result from ongoing antigenic stimulation .…”
Section: Discussionmentioning
confidence: 99%